Identification of Asnaf in distress: netizens' roles - Mohd. Zain, Nor Razinah; Ashurov, Sharofiddin; Mohd Noor, Azman (2020)
Introduction: The increasing use of internet leads to several online communication platforms. In Malaysia, online communication platforms such as Facebook, Instagram, and Twitters are among the most frequent visited by Malaysians. Many religious institutions including Zakat institutions also have their own official online communication platforms. This is taken as the latest trend where a direct communication and engagement can be done between the said institution and the public. Nowadays, the term ‘netizens’ are used to indicate the public that uses the online communication. Materials and method: By adopting the qualitative investigation, this research evaluates the increasing role of netizens in reporting cases of needy asnafs i.e. the eligible people that qualified to receive Zakat. The researchers evaluate the trend from the Zakat institutions that have their official online communication platforms. Results: It is found that there is an increasing role of netizens in reporting cases of Asnafs that are facing financial distress that required an immediate assistance and attention from the Zakat institutions. However, there are also a lot of fake news and reporting that directly and indirectly impacting the good reputation of Zakat institutions. Such fake nes and reporting should be prevented. Conclusion: The online communication platforms increase the reporting of Asnafs that are facing financial distress from netizens. Such kind of reporting is important and necessary for quick and immediate distribution of Zakat to the Asnafs.